Chemical Contaminants of Water and Human Health Consequences - Patil, Shreya R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Safe drinking water is from an improved water source that is located on premises, available when needed and free from faecal and priority chemical contamination. To achieve the highest level of health, the drinking water must be safe, accessible, and with proper sanitation. People depend on clean drinking water to survive; it is also necessary for recreation, bathing, cooking and cleaning. The review focuses on to identify the main chemical contaminants, their sources and the associated health impacts. Data published in reputed academic journals was reviewed and used for present study. Results of the study reveals that water can be contaminated due to domestic sewage, industrialization, pesticides and fertilizers, plastics, population growth, urbanization, and weak management system. Major chemical contaminants of water are agricultural chemicals, emerging chemical contaminants, industrial chemicals, naturally occurring chemicals, and sanitation system chemicals and by-products. It is observed that; various types of chemicals such as, agricultural, emerging contaminants, industrial, naturally occurring, and sanitation system and by-products acts a major pollutants of water pollution. Sources of groundwater are regularly monitored and preventive measures should be practiced to reduce the harmful effects. The water quality can be improved by reducing pollution, eliminating dumping and minimizing release of hazardous chemicals and materials. Industrial wastes, especially the chemicals must be treated before their disposal. Future study should be focussed on to develop a technique for early detection of chemical pollutants in water. Also it is important to improve the current practices on prevention and remediation techniques for water pollution.